The first reported ceratopsid dinosaur from eastern North America (Owl Creek Formation, Upper Cretaceous, Mississippi, USA) - Farke, Andrew A.; Phillips, George E. (PeerJ Preprints, 2017)
Ceratopsids (“horned dinosaurs”) are known from western North America and Asia, a distribution reflecting an inferred subaerial link between the two landmasses during the Late Cretaceous. However, this clade was previously unknown from eastern North America, presumably due to limited outcrop of the appropriate age and depositional environment as well as the separation of eastern and western North America by the Western Interior Seaway during much of the Late Cretaceous. A dentary tooth from the Owl Creek Formation (late Maastrichtian) of Union County, Mississippi, represents the first reported occurrence of Ceratopsidae from eastern North America. This tooth shows a combination of features typical of Ceratopsidae, including a double root and a prominent, blade-like carina. Based on the age of the fossil, we hypothesize that it is consistent with a dispersal of ceratopsids into eastern North America during the very latest Cretaceous, presumably after the two halves of North America were reunited following the retreat of the Western Interior Seaway.
Keywords: Ceratopsia; biogeography; Laramidia; Appalachia; Ceratopsidae; Dinosauria; Owl Creek Formation; Cretaceous; dinosaur; Western Interior Seaway